Association of mental health status with quality of life among medical students in IIUM during COVID-19 - Mohamad, Mohammad Muaz; Johari, Muhammad Luqman ‘Afif; Zulkifli, Ahmad Najmi Abid; Abdullah, Muhammad Haikal; Razman, Amalia Izzati; Shaik Mohd Nizam, Nur Alia Iman; Ahmad Ashhar, Muhammad Ikmal Arif; Ahmad Haridan, Ahmad Zhareff Emir; Nor Azlan, Nur Khairunnisa; Shahrir, Shahida Athirah; Anuar, Muhammad Ashraf Fithri; Zamani, Muhammad Razin; et al. (2021)
The existence of COVID 19 has significantly changed humans daily life in this world. The new norm of living in this pandemic has also led to a different approach on managing quality of life. With the current method of online teaching and learning, medical students may encounter a variety of stressors such as heavy workload, stressful examination and also inadequate learning environment which may influence their mental health. This study is conducted to investigate the association of mental health status with quality of life among medical students in International Islamic University Malaysia (during the pandemic. A cross-sectional study was conducted online among 158 medical students of Year 1 and Year 2 between July and August 2021. This survey used validated questionnaires to assess depression (WHO 5 anxiety (GAD 5 and Quality of Life BREF (WHOQOL BREF) WHOQOL BREF measures five domains: overall quality of life (physical health, psychological health, social relationships, and environmental quality of life. The result was analysed using Statistical Package for the Social Sciences (SPSS) version 26. The prevalence rates of anxiety and depression-related symptoms were 27.8% and 86.7% respectively with more students developing anxiety as compared to depression. The proportion of students with anxiety was higher than depression in both Year 1 (n=67) and Year 2 (n=70) students. Students with anxiety and depression symptoms had a significantly poorer overall QOL score (p<0.001) compared to students without mental health problems. Both categories of students were associated with lower physical, psychological and environmental domain scores (p<0.05). In conclusion, the quality of life of medical students are significantly affected by the presence of anxiety and depression. Progressive strategies need to be implemented to maintain good mental health care among medical students in IIUM as it will improve their quality of life during Covid-19.